Process oriented data virtualization design model for business processes evaluation (PODVDM) research in progress - Mousa, Ayad Hameed; Shiratuddin, Norshuhada; Abu Bakar, Muhamad Shahbani (Penerbit UTM Press, 2015)
During process enactment in the business process management (BPM) lifecycle, information collected on execution plans are stored in the form of log files and database tables by using information systems (IS).In the past decade, a new approach based on the applications of Business Intelligence (BI) in business process management has emerged. The approach implements process-oriented data warehouse and mining techniques.However, the main issue is providing the right information at the right time to facilitate process evaluation that can be used for performance analysis and improve business process.Existing techniques have limitations, including huge data in database log files, performance of Process Warehouse (PW), which is highly dependent on specific design), complexity of PW design, lack of convergence between business processes and PW specifications, and the need for real data during process evaluation stage.Objects such as processes, storage, and data repositories can be virtualized to address these limitations.The main aim of this study is to propose a process-oriented data virtualization design model for process evaluation in BPM.The model will be validated through expert reviews and prototype development as well as through a case study.In this paper, we describe the research motivation, questions, approach, and methodology related to addressing the described limitations by designing a model for evaluation in business processes using the Data Virtualization technique.